Analisis Pengaruh Kualitas Produk dan Harga dalam Keputusan Pembelian Sepeda Motor Honda Scoopy di Kabupaten Cirebon - Elsa, Khofifah; Chandra, Aditya Kurniawan; Pranata, Sudadi (Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine whether (1) there is a positive relationship between product quality on purchasing decisions for Honda Scoopy motorcycles, (2) the effect of price on purchasing decisions for Honda Scoopy motorcycles and (3) the effect of product quality and price simultaneously on purchasing decisions of bicycles. Honda Scoopy in Cirebon district. The population in this study were residents of several sub-districts in Cirebon district who had Honda Scoopy automatic motorcycles. The sampling technique used the slovin formula with a total sample of 100 people with 20 people per sub-district. The data collection technique uses a Google Form questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple linear regression. The results showed that: (1) there was a positive effect of product quality on purchasing decisions for Honda Scoopy motorcycles (t count 4,457; sig. 0.000 0.05; = 0.210) , (2) there was a positive influence on price on motorcycle purchasing decisions. Honda Scoopy ((t count 4.029; sig. 0.000 0.05; = 0.94), (3) ) there is a positive effect of product quality and price simultaneously on purchasing decisions for Honda Scoopy motorcycles (F count = 60.609; Sig. .000 0.05) .Keywords: product quality, price and purchase decision.